Antioxidant Properties of Albumin and Diseases Related to Obstetrics and Gynecology - Kazushi Watanabe; Hiroyuki Kinoshita; Tomohito Okamoto; Kazumasa Sugiura; Shingo Kawashima; Tetsuro Kimura (Antioxidants)
Albumin, the most abundant protein, contributes significantly to various physiological processes, indicating its multifunctional properties. It has drawn the attention of scientists and physicians because of its primary role in maintaining osmotic pressure and involvement in transporting numerous small molecules, including hormones, fatty acids, and drugs. A growing body of evidence has recently illustrated an additional aspect of albumin’s antioxidant properties. Therefore, based on recent research findings, this review article delves into the molecular and biochemical aspects of albumin’s antioxidative capabilities. We highlight the multifaceted significance of proteins in oxidative stress and their relation to pathologies in obstetrics and gynecology. In particular, we focused on preeclampsia, in which oxidative stress is closely involved in the pathogenesis, and renal dysfunction leads to increased albumin excretion into the urine, resulting in hypoalbuminemia. In addition, we discussed the role of albumin in preeclampsia pathogenesis, diagnosis, and patient prognosis. Understanding the antioxidant properties of albumin opens new avenues for therapeutic intervention and sheds light on novel strategies for combating preeclampsia associated with oxidative damage. In this study, we employed the PubMed database to search for articles that assessed the antioxidant properties of albumin, with a specific focus on obstetric diseases, particularly preeclampsia. The last update of the search was conducted in November 2024.